Metaphor “life-formation” and its connection with other basic metaphors in the narrative by A.P. “My life” (Proceedings of Southern Federal University. Philology, 2015)
The article studies the implementation of the conceptual metaphor of life - in the structure of the novel by A.P. Chekhov “My Life”. It is analyzed the relationship with a number of other complexes of metaphorical story (life - road for the flight, sleep), traced their deployment in object-verbal part of the story and semantic plexus in complex linguistic fabric of the text. This method of the study facilitates the comprehension of the aesthetic values of linguistic units text and its deeper meaning. The analysis proves that the building metaphor in the novel “My Life” gives rise to one of the most important ways of life of public order. It shows the deployment of man’s place in public buildings, describing his lifestyle and determining the spiritual condition as a deathly, devoid of life. In a sign of the horizontal and static position in space it is connected with the metaphor of life - sleep, oblivion. With the introduction of life in the form of road construction metaphor enters into a relationship of opposition: they are differently based on whether the movement and its absence, as well as natural and artificial, life in its ontology and its phenomenology, as the embodiment of the object of human activity. Metaphors flow and flight - to a certain extent overlapping images of a person’s life non-self-managed - together with the idea of life as building a complete picture of real-life human life. It does not change in its essence with all the fullness of its social movements of different kinds of thoughts and ideas that come to replace one another.Keywords: Chekhov, concept, life, structure, road, water, sleep.Scharenskaya Natalya Markovna - candidate of linguistics, professor assistant of the Russian language dpt. Institute of philology, journalism and cross-cultural communication, Southern federal university. Phone: 8-863 -2 913-133, 8-918-511-48-86; e-mail: n-scharenskaja@yandex.ru